Identifying Quality Gaps in Preventive Care for Outpatients With Cirrhosis Within a Large, Academic Health Care System. Issue 12 (9th September 2020) - Kardashian, Ani; Patel, Arpan A.; Aby, Elizabeth S.; Cusumano, Vivy T.; Soroudi, Camille; Winters, Adam C.; Wu, Eric; Beah, Peter; Delshad, Sean; Kim, Nathan; Yang, Liu; May, Folasade P.
Abstract : We sought to identify specific gaps in preventive care provided to outpatients with cirrhosis and to determine factors associated with high quality of care (QOC), to guide quality improvement efforts. Outpatients with cirrhosis who received care at a large, academic tertiary health care system in the United States were included. Twelve quality indicators (QIs), including preventive care processes for ascites, esophageal varices, hepatic encephalopathy, hepatocellular carcinoma (HCC), and general cirrhosis care, were measured. QI pass rates were calculated as the proportion of patients eligible for a QI who received that QI during the study period. We performed logistic regression to determine predictors of high QOC (≥ 75% of eligible QIs) and receipt of HCC surveillance. Of the 439 patients, the median age was 63 years, 59% were male, and 19% were Hispanic. The median Model for End‐Stage Liver Disease–Sodium score was 11, 64% were compensated, and 32% had hepatitis C virus. QI pass rates varied by individual QIs, but were overall low. For example, 24% received appropriate HCC surveillance, 32% received an index endoscopy for varices screening, and 21% received secondary prophylaxis for spontaneous bacterial peritonitis. In multivariable analyses, Asian race (odds ratio [OR]: 3.7, 95% confidence interval [CI]: 1.3‐10.2) was associated with higher QOC, and both Asian race (OR: 3.3, 95% CI: 1.2‐9.0) and decompensated status (OR: 2.1, 95% CI: 1.1‐4.2) were associated with receipt of HCC surveillance. A greater number of specialty care visits was not associated with higher QOC. Conclusion: Receipt of outpatient preventive cirrhosis QIs was variable and overall low in a diverse cohort of patients with cirrhosis. Variation in care by race/ethnicity and illness trajectory should prompt further inquiry into identifying modifiable factors to standardize care delivery and to improve QOC. Abstract : This study examines the quality of outpatient preventive care in a large, ethnically diverse cohort of outpatients with cirrhosis at a high‐volume tertiary liver transplant center. Receipt of evidence‐based quality indicators, including preventive processes for ascites, esophageal varices, hepatic encephalopathy, hepatocellular carcinoma, liver transplantation, and general cirrhosis care, was variable and overall low. These findings suggest that larger system redesign efforts are needed to improve the quality of care, beyond just improving access to specialty providers.